Student engagement in university decision-making and governance : towards a more systemically inclusive student voice 2015-2016 : international research report 2015. - Varnham, Sally (Australia. Dept of Education and Training (DET), 2018)
Through the University of Technology Sydney's (UTS) Professional Experience Program (PEP), chief investigator Sally Varnham had the opportunity to conduct research into student engagement in the United Kingdom, Belgium and New Zealand. Interviews and focus groups were conducted. Funded by the University of Technology Sydney, this investigation has become a foundation item of research for the OLT project led by Professor Varnham exploring and promoting the benefits of student engagement in university decision-making and governance. This report is part of a set of four publications on the topic. The other publications are a project final report, survey report and good practice case studies report. This report details the project findings relating to how student engagement in university decision making and governance operates in comparative sectors internationally. The goal is to inspire a sector-wide conversation and ultimately, a collaboration to agree a set of principles and a framework for good practice in Australian universities. [Executive summary, ed]